Controlled Release Dosage Form for Once Daily Administration of Dimethyl Fumarate (2018)
A controlled release dosage form containing monomethyl fumarate, a compound that can be metabolized into monomethyl fumarate in vivo, or a pharmaceutically acceptable salt thereof or combinations thereof wherein the monomethyl fumarate, a compound that can be metabolized into monomethyl fumarate in vivo, or a pharmaceutically acceptable salt thereof or combinations thereof is delivered to the subject. Also provided is a method of treating a disease or disorder (e.g., multiple sclerosis) by orally administering a controlled release dosage form containing monomethyl fumarate, a compound that can be metabolized into monomethyl fumarate in vivo, or a pharmaceutically acceptable salt thereof or combinations thereof, wherein the monomethyl fumarate, a compound that can be metabolized into monomethyl fumarate in vivo, or a pharmaceutically acceptable salt thereof or combinations thereof.